Consistent condom use and its correlates among female sex workers at hair salons: a cross-sectional study in Zhejiang province, China - Qiaoqin Ma; Jianmin Jiang; Xiaohong Pan; Gaofen Cai; Hui Wang; Xin Zhou; Tingting Jiang; Lin Chen (BMC, 2017)
Abstract Background This study investigated condom use among female sex workers (FSWs) at hair salons during commercial sexual interactions over 1 month. We explored the associations of such use with various sexual behaviours, HIV/STI risk perception and related knowledge, self-efficacy regarding condom use, exposure to behavioural interventions, and other factors. This type of information has not been reported in China and is critical for designing and modifying programs aimed at preventing HIV/STI transmission in this group of FSWs and their clients. Methods Our data were derived from a large cross-sectional study conducted among low-tier FSWs in 21 counties within Zhejiang province, China. Data were collected from September to November 2013.Bivariable and multiple logistic regression analyses were used to identify factors associated with self-reported consistent condom use among FSWs working at hair salons. Results Of 1682 FSWs working at hair salons, 50.5% consistently used condom with clients during the previous month. Multivariable analysis revealed that condom use for commercial sex, consistent vaginal douching after commercial sex, adopting contraceptive measures, high scores on perceived self-efficacy regarding condom use, and exposure to interventions were associated with self-reported consistent condom use; early initiation of commercial sex, experiences with oral sex, rarely/sometimes/often using oral contraceptives, and having seen a doctor were associated with not using condoms. Conclusions Commercial sex is not effectively protected, and behavioural interventions targeting FSWs should take into account the various factors that are correlated to condom use.